Efficiency improvement of fatigue crack healing by multiple high-density pulsed electric currents: Application to austenitic stainless steel. (19th May 2023) - Yoon, Sungmin; Gu, Shaojie; Li, Shaoli; Kimura, Yasuhiro; Toku, Yuhki; Ju, Yang
Graphical abstract: Highlights: This study aims to comprehensively provide a novel approach for the efficiency improvement of fatigue crack healing in austenitic stainless steel. Multiple high-density pulsed electric currents were investigated for fatigue crack healing. Appropriate application methods were examined and applied to fatigue crack healing under controlled crack tip temperature elevation owing to the Joule heating. The results revealed microstructural improvements for short cracks such as crack closure with bridging, flattening slip bands, and material filling near the crack tips. Fatigue crack healing with improved microstructure could correspondingly yield fatigue crack growth delays. Abstract: This study aims to demonstrate the use of a novel treatment approach for fatigue crack healing. High-density pulsed electric currents, which have been widely used for fatigue crack healing of metals, can exert synergistic effects on fatigue crack healing by both compressive stress (owing to the Joule heating) and dislocation motion (owing to the electron wind force). However, these synergistic effects are sometimes weakened by temperature elevations owing to high current densities, failing to efficiently heal fatigue cracks owing to the thermal degradation of metals. In this study, type 316 austenitic stainless steel, which is the most common metallic material, was considered for investigating fatigue crack healing improvement under controlled crack tip temperature elevation owing to the Joule heating induced by multiple high-density pulsed electric currents. Appropriate current parameters such as current density and pulse number under fixed pulse duration were optimized. The results revealed microstructural modifications, such as crack closure with crack bridging, annihilation of slip bands, and material filling near the crack tips, which is promising for fatigue crack healing improvement. The results of fatigue crack growth tests validated these microstructure improvements.